Elementary School Literacy Facilities Index: Analysis of Availability and Its Implications for the School Literacy Movement in Cianjur - Tita Hasanah; Abdul Talib Bin Mohamed Hashim (Global READ Center, 2026)
This study aims to analyze the literacy facilities index in elementary schools in Cianjur and its implications for the implementation of the School Literacy Movement (SLM). The study employed a quantitative approach with a descriptive survey method involving 91 schools. Data were collected through a questionnaire covering four components: physical literacy facilities, school literacy media, reading resources, and digital literacy facilities, and were analyzed using mean scores and index calculations. The results show that the overall literacy facilities index is 3.15 (fair category). School literacy media (3.54) and reading resources (3.45) are categorized as good, digital literacy facilities (3.04) are fair, while physical literacy facilities (2.67) are the lowest. The limited availability of physical literacy facilities, particularly libraries and laboratories, restricts students’ access to learning resources and constrains the development of sustainable literacy environments, thereby hindering the effective implementation of the School Literacy Movement. Therefore, policies should prioritize the equitable provision and optimal utilization of physical literacy facilities to strengthen its implementation. These findings highlight the importance of addressing facility disparities in supporting school literacy programs.